Measuring the magnetic field of a low frequency LC-circuit with phyphox. (1st November 2022) - Westermann, N; Staacks, S; Heinke, H; Möhrke, P
Abstract: In high school, LC(R)-circuits are an integral component of physics education. We propose a new setup for exploring those circuits utilizing the magnetic field sensor of a smartphone in combination with the application phyphox, which reads and displays sensor input. Coils with high inductance and low resistance generate low frequency oscillations which can be visualized without any measuring devices other than a smartphone. The results are very satisfactory, because the resolution of the graph is high and the theoretical values match principal features of the measurements. Also, the setup can be achieved with low-cost components.